Management Strategies and Outcomes for Hyponatremia in Cirrhosis in the Hyponatremia Registry - Samuel H. Sigal; Alpesh Amin; Joseph A. Chiodo; Arun Sanyal (Canadian Journal of Gastroenterology and Hepatology)
Aim. Treatment practices and effectiveness in cirrhotic patients with hyponatremia (HN) in the HN Registry were assessed. Methods. Characteristics, treatments, and outcomes were compared between patients with HN at admission and during hospitalization. For HN at admission, serum sodium concentration [Na] response was analyzed until correction to > 130 mmol/L, switch to secondary therapy, or discharge or death with sodium ≤ 130 mmol/L. Results. Patients with HN at admission had a lower [Na] and shorter length of stay (LOS) than those who developed HN (P < 0.001). Most common initial treatments were isotonic saline (NS, 36%), fluid restriction (FR, 33%), and no specific therapy (NST, 20%). Baseline [Na] was higher in patients treated with NST, FR, or NS versus hypertonic saline (HS) and tolvaptan (Tol) (P < 0.05). Treatment success occurred in 39%, 39%, 52%, 78%, and 81% of patients with NST, FR, NS, HS, and Tol, respectively. Relapse occurred in 55% after correction and was associated with increased LOS (9 versus 6 days, P < 0.001). 34% admitted with HN were discharged with HN corrected. Conclusions. Treatment approaches for HN were variable and frequently ineffective. Success was greatest with HS and Tol. Relapse of HN is associated with increased LOS.